T-overlap T-migrative Functions: a generalization of migrativity in t-overlap functions - Zapata Ceballos, Hugo Alain; Bustince, Humberto; Dimuro, Graçaliz Pereira (Revista Científica, 2020)
This paper introduces a generalization of migrative functions by extending the conditions of the product operation applied in the variables. More specifically, instead of requiring to multiply the variable x by a real number α; in this work we operate this α number with the variables according to a t-norm. We call such generalization as a t-migrative function with respect to such t-norm. Then we analyze the main properties of t-migrative t-overlap functions and introduce some construction methods.